AB1150 The european reference network on rare and complex connective tissue and musculoskeletal diseases: ern reconnet. (12th June 2018) - Mosca, M.; Cutolo, M.; Badreh, S.; Bombardieri, S.; Burmester, G.; Fonseca, J.E.; Frank, C.; Galetti, I.; Hachulla, E.; Houssiau, F.; Müller-Ladner, U.; Schneider, M.; et al.
Abstract : Background: Set up under the European Union (EU) directive on patients' rights in cross-border healthcare (2011/24/EU), European Reference Networks (ERNs) on rare and complex diseases are aimed at connecting healthcare providers (HCPs) across different EU Countries to tackle complex and rare medical conditions that require highly specialised treatment. ERN ReCONNET, endorsed by EULAR, and approved for rare and complex connective tissue diseases (CTDs), aims at developing a framework for the delivery of high quality, innovative, sustainable and equitable standard of care and practice for better access to care of European patients. Objectives: To report the activities of ERN ReCONNET during the first 10 months of work Methods: ERN ReCONNET is composed of 26 HCPs from 8 EU Countries: Belgium, France, Germany, Italy, Netherlands, Portugal, Romania and Slovenia. Patients involvement is ensured by the ERN ReCONNET European Patients Advocacy Group, included in the activities of the ERN. The diseases covered are divided into 3 main thematic areas: rare CTDs (systemic sclerosis, mixed CTD, idiopathic inflammatory myopathies, antiphospholipid syndrome, undifferentiated CTD, IgG4 related diseases, relapsing polychondritis), complex CTDs (SLE, Sjogren's Syndrome), hereditary connective tissue diseases (Ehlers-Danlos syndrome). Senior and Junior Coordinators for each disease were selected. The scientific activities of ERN ReCONNET officially started in Vilnius in March 2017, where the 24 ERNs have been formally launched. Results: The scientific activities of the first year were mainly focused on existing clinical practice guidelines (CPGs). The first phase was aimed at identifying the scientific publications, selecting them by evaluation of titles and abstracts, and by reviewing the full texts. More than 6.000 publications have been screened. The second step was to review critically the articles according to the principles of the AGREEII flow-chart. This work allowed to identify CPG for the majority of the diseases covered by ERN ReCONNET, as well as unmet needs, in particular for the rarest diseases (IgG4 related diseases, relapsing polychondritis, mixed CTD). Good progress has also been made in the field of IT, in which ERN ReCONNET was mainly focused on the use of the Clinical Patients Management System web-platform, designed for the interactive discussion of difficult clinical cases. Notably, the creation of ERN website is being co-designed by all Networks stakeholders. Conclusions: The ERN ReCONNET will significantly improve the clinical approach to rare and complex CTDs, promoting an improvement of the quality of the specialised care provided to patients, of the activity of the physicians, the empowerment of the patients sharing expertise and promoting the interaction among EU HCPs. All these activities are addressed to create a highly specialised network, in which the knowledge travels rather than the patient. Disclosure of Interest: None declared